An update on sleep in bipolar disorders: presentation, comorbidities, temporal relationships and treatment. (August 2020) - Morton, Emma; Murray, Greg
Abstract : Sleep and circadian rhythms have been implicated in the onset, course, and treatment of bipolar disorder. The aim of the present review is to provide an update on emerging understandings of the role of sleep in BD. Recent research in this population has provided further clarity around the prevalence of sleep problems and comorbidities, their relationship to mood symptoms and other clinical features, and their assessment and treatment. A number of important trends are highlighted: the need for more granularity in the characterisation of sleep problems, the potentially disruptive role of commercial sleep monitoring technologies in assessment and treatment, and the urgent need for further research into pharmacological and psychosocial strategies to treat sleep problems in bipolar disorder.